Performance Evaluation of Targeted Public Distribution System (TPDS) - Planning Commission (Planning Commission, 2005)
The Targeted Public Distribution System (TPDS) is an important instrument of policy aimed at reducing poverty through the mechanism of delivering minimum requirements of food grains at highly subsidised prices to the population below the poverty line. To assess its efficiency and effectiveness in achieving this objective, the Planning Commission and the Ministry of Consumer Affairs, Food and Public Distribution initiated an independent evaluation of performance by the Programme Evaluation Organisation (PEO). The evaluation used relevant process data collected from the various nodes of the delivery system and also relied upon a sample survey of fair price shops and households spread over 18 States and has come up with some far-reaching findings and observations. The study finds that about 58 per cent of the subsidized food grains issued from the Central Pool do not reach the BPL families because of identification errors, non-transparent operation and unethical practices in the implementation of TPDS. The cost of handling of food grains by public agencies is also very high. According to the study.
Implementation Results Development Intervention Input Activities Output Outcome Impact